The Role and Importance of Extracurricular Activities in the Formation of Moral Education - qizi, Sattorova Dilfuza Bahadir (Research Parks Publishers, 2023)
In this article, the role and importance of extracurricular educational activities in the formation of spiritual and moral education in the school is scientifically and theoretically analyzed.